2021
DOI: 10.1038/s41398-021-01295-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of neuroimaging and acute cannabis exposure in age-of-risk for psychosis

Abstract: Acute exposure to cannabis has been associated with an array of cognitive alterations, increased risk for neuropsychiatric illness, and other neuropsychiatric sequelae including the emergence of acute psychotic symptoms. However, the brain alterations associating cannabis use and these behavioral and clinical phenotypes remains disputed. To this end, neuroimaging can be a powerful technique to non-invasively study the impact of cannabis exposure on brain structure and function in both humans and animal models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Neuroimaging studies in cannabis users showed a decreased brain metabolic activity in several brain regions after acute cannabis expose as well as after short periods of abstinence (Block et al 2000;Lundqvist et al 2001;Eldreth et al 2004;Sevy et al 2008;Cupo et al 2021). However, the cerebral metabolism pattern after long periods of abstinence has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies in cannabis users showed a decreased brain metabolic activity in several brain regions after acute cannabis expose as well as after short periods of abstinence (Block et al 2000;Lundqvist et al 2001;Eldreth et al 2004;Sevy et al 2008;Cupo et al 2021). However, the cerebral metabolism pattern after long periods of abstinence has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to reconcile the neuroimaging with neuropsychological test performance. 50,58,59 Although yet unknown, neuropsychological tests may improve or recover with prolonged abstinence, as this has been observed in some studies but not others. 51,60 The age of onset of cannabis use, as well as frequency and duration of use likely all impact recoverability.…”
Section: Psychiatric Effectsmentioning
confidence: 93%
“…Although the poor neuropsychological functioning in association with cannabis use in children has been consistently proven, the literature has been inconsistent in demonstrating the negative impact of cannabis on neuroimaging. Further studies are needed to reconcile the neuroimaging with neuropsychological test performance 50,58,59 …”
Section: Cannabidiolmentioning
confidence: 99%
“…Administering THC in otherwise healthy humans elicits key symptoms of PSD, including delusional thought content ( Kleinloog et al, 2014 ). Similar to both ketamine and LSD, THC also perturbs large-scale neural system organization, and reproduces thalamocortical dysconnectivity to some extent ( Camchong et al, 2017 ; Cupo et al, 2021 ).…”
Section: Evidence For Thalamocortical Circuit Alterations In Psychosi...mentioning
confidence: 99%